Aplikasi Diagnosis Tingkatan Pneumonia dan Saran Pengobatan dengan Fuzzy Tsukamoto - Elyza Gustri Wahyuni; Ahmad Syahriza Ramadhan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Pneumonia is a disease that attacks almost every human being, ranging from young people to adults. Doctors often find it difficult to identify someone who has pneumonia, because pneumonia has several levels of classification, making it possible to experience symptoms that are also different. Pulmonary specialist experts classify pneumonia classification to be "mild" and "severe", making it easier for doctors to diagnose pneumonia. One of the right methods is to use fuzzy logic because it tends to have symptoms and diagnoses that are biased/fuzzy. The conclusion of testing several primary data obtained from interviews and system testing is that the implementation of the pneumonia diagnosis system with Tsukamoto fuzzy logic can help experts determine the level of pneumonia according to the symptoms experienced by the patient, with the value of user acceptance testing at 95%.